Prevalence of pelagic diatoms and harmful algae in tellinid bivalve diets during record low sea ice in the Pacific Arctic determined by DNA metabarcoding - Koch, Chelsea W.; Sonsthagen, Sarah A.; Cooper, Lee W.; Grebmeier, Jacqueline M.; Riddle-Berntsen, Ann E.; Cornman, Robert S. (Frontiers in Marine Science, 2025)
Understanding changes at the base of the marine food web in the rapidly transforming Arctic is essential for predicting and evaluating ecosystem dynamics. The northern Bering Sea experienced record low sea ice in 2018, followed by the second lowest in 2019, highlighting the urgency of the issue for this region. In this study, we investigated the diet of the clam Macoma calcarea in the Pacific Arctic using DNA metabarcoding, employing 18S and rbcL markers to identify dietary components. Our findings revealed a strong dependence on pelagic diatoms, particularly Chaetoceros sp., with a near absence of ice algae in the clam diet. This pattern reflects the lack of lipid-rich ice algal production during these low sea ice events. Additionally, our analysis detected algae capable of producing harmful toxins, notably Alexandrium dinoflagellates, in the clam diet, underscoring the need for increased monitoring due to potential ecosystem and human health risks. This study demonstrates the utility of DNA metabarcoding in unraveling the complex dynamics of Arctic marine food webs and pelagic-benthic coupling, providing a glimpse of future conditions in a rapidly changing environment.